Comparison of Accuracy of Conventional Periapical Radiography and Direct Digital Subtractions Radiography with or without Image Enhancement in the Diagnosis of Density Changes - Tahmineh Razi; Arezu Mohammadi; Morteza Ghojazadeh (Tabriz University of Medical Sciences, 2012)
Background and aims. In periapical radiographic technique, the changes will be visible only after considerable deposition or resorption while digital subtraction technique visualizes slight density changes. This study was aimed to compare visualization of density changes in conventional periapical radiographs and digital subtraction technique with or without image enhancement. Materials and methods. Three dry human mandibles with unspecified age and gender were selected. Conventional periapical and direct digital radiographs were taken from the anterior, and right and left posterior regions by step-wise placement of aluminum plates until the image of the plate was clearly visible. The radiographs taken with the direct digital technique were subtracted from the first radiograph using Photoshop software. Three observers evaluated the radiographs and the digital subtraction images with or without image enhancement. The density was recorded in each radiograph in which the image of the aluminum plate was completely visible. Results. In all mandibles, the differences in diagnosis of density changes between the conventional periapical radiographic technique and the direct digital subtraction radiographic technique with or without image enhancement were statistically significant irrespective of the region under study (p<0.001). There were no significant differences in the diagnosis of density changes in all the three mandibles in the left and right posterior regions between the two radiographic techniques. However, the differences in the anterior region were statistically significant (p<0.001). Conclusion. Direct digital subtraction radiographic technique with or without image enhancement is a more efficacious technique in exhibiting minor density changes compared to conventional periapical radiographic technique